The marginal nation - Samāddāra, Raṇabīra, author. Link
1 online resource
Keywords: "The Marginal Nation analyses the realities of transborder migration in the South Asia region going beyond the domains of economics and demography. It provides an in-depth look into the historical, cultural and geographic dimensions of migration across the India-Bangladesh border that challenges fixed definitions of borders, nations and identities. Drawing from extensive fieldwork, the author encapsulates the lives and aspirations of migrants exploring the social affinities and historical ties that bind people across territories and 'marginalises' national identity. The book chronicles the lived experiences of migrants and their everyday lives, conflicts and contradictions. It pits these narratives against 'national' concerns over security, statehood, and demarcated borders interrogating their immutability in the South Asian context. This revised edition reflects upon the significance and relevance of the book to migration and refugee studies in South Asia and beyond twenty-five years after it was first published. A classic, this book will be of interest to students and scholars in the fields of political science, sociology, history, human rights studies, refugee studies, demography and South Asian studies"--